Management Of Underweight Monitoring In Prevention Of Underweight In Tanjung Jabung Timur District, Jambi, Indonesia - Ena Sari, Rumita; Ismi Nurwaqiah Ibnu; Herlambang , Herlambang (Sean Institute, 2024)
One form of malnutrition in infants and toddlers is underweight, which is a condition in which the body weight of infants or toddlers is far below their age standard. Based on the SSGI results, the prevalence of underweight in Jambi Province reached 13.8% in 2022, and the highest district/city prevalence of underweight was East Tanjung Jabung District with a prevalence of 21%. This study aims to analyzed the management of monitoring the weight children in an effort to prevent underweight. This research was qualitative study with 11 informants. Informants were selected using purposive technique. Data collected by indepth interview. Data analyzed by content analysis. Based on in-depth interviews, the input component consisting of human resources and infrastructure has not been maximized. The process component of monitoring under-two children was not in accordance with procedures, and the output component has not obtained accurate children monitoring data. It is recommended that regular monitoring of the progress of weight monitoring of underweight children, training health centre staff as information management personnel, increasing the participation of cadres by providing adequate incentives, and periodic reporting can be used as input in the prevention and intervention of underweight children.